KOMUNIKASI INSTRUKSIONAL GURU KETERAMPILAN DALAM MENINGKATKAN KEMAMPUAN MEMBATIK PADA SISWA TUNARUNGU JENJANG SEKOLAH MENENGAH ATAS (SMA) DI SEKOLAH LUAR BIASA NEGERI PEMBINA KOTA PEKANBARU - Erdiyanto "; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Batik skills lesson is one of the vocational lessons followed by deaf students at the Senior High School (SMA) level at SLBN Pembina Pekanbaru City. The condition of deaf students who have hearing impairments and the lack of vocabulary and communication makes the learning process not easy, the media and methods are adapted to the students' conditions. Therefore, the teacher uses instructional communication in order to change the behavior of students to be able to master the batik skills material. The purpose of this study was to find out the learning methods used, learning media and communication barriers that occurred during batik learning at SLBN Pembina Pekanbaru. This study used qualitative research methods. The subjects in this study were school principals, teachers, students and guardians of SLBN Pembina Pekanbaru who were selected using a purposive technique. Data collection techniques consist of observation, interviews, and documentation. Meanwhile, the data analysis technique uses interactive analysis according to Miles and Huberman. The data validation technique used in this study is the extension of participation and triangulation. The results showed that the teacher's instructional methods in learning batik were divided into sign language, oral, total communication and direct practice or demonstration methods. Batik learning media in the form of audio, visual, and audio visual media. Instructional communication barriers in learning include obstacles to teachers, namely difficulties in communicating with students due to difficulties in providing understanding and explanations to students so they can understand the material provided, and obstacles to students, namely due to limited vocabulary they have, and understanding the meaning of the teacher's skills batik due to lack of hearing. The results of this study can be used as reference material for SLBN Pembina Pekanbaru to develop learning that is more interesting and more varied in the future.